Proximity Labeling Techniques: A Multi-Omics Toolbox - Olha Viktorivna Shkel; 예브헤니아 하르키브스카; Kim, Yun Kyung; Lee, Jun-Seok (WILEY-V C H VERLAG GMBH, 2022)
Proximity labeling techniques are emerging high-throughput methods for studying protein-protein, protein-RNA, and protein-DNA interactions with temporal and spatial precision. Proximity labeling methods take advantage of enzymes that can covalently label biomolecules with reactive substrates. These labeled biomolecules can be identified using mass spectrometry or next-generation sequencing. The main advantage of these methods is their ability to capture weak or transient interactions between biomolecules. Proximity labeling is indispensable for studying organelle interactomes. Additionally, it can be used to resolve spatial composition of macromolecular complexes. Many of these methods have only recently been introduced; nonetheless, they have already provided new and deep insights into the biological processes at the cellular, organ, and organism levels. In this paper, we review a broad range of proximity labeling techniques, their development, drawbacks and advantages, and implementations in recent studies.